The Effect of Consumer's Feeled Values on Continuous Purchase Intention and Trust in Streamers as Mediation in E-Commerce Live-Streaming - Sari, Aida; Nabila, Nuzul Inas; Marvinita, Risda; Azzahra, Nyimas Latifah (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
This study examines the influence of consumer perceived value on repeat purchase intention in live-streaming e-commerce, considering the mediating role of consumer trust. Based on the stimulus-organism-response (SOR) model, this study examines how stimuli in the form of utilitarian values, such as product quality, hedonic value, social value, and symbolic value offered by streamers in live streaming can trigger a psychological response in the form of consumer trust. This trust is hypothesized to mediate the relationship between these values and repeat purchase intentions. Using a quantitative approach with a sample of 205 respondents active in live streaming e-commerce, the results show that the four values perceived by consumers significantly affect trust in the streamer. Furthermore, this trust is shown to mediate the relationship between these values and repeat purchase intentions. These findings underscore the importance for streamers to focus not only on the functional aspects of the product (utilitarian value) but also on the emotional (hedonic value), social (social value), and symbolic (symbolic value) aspects in building strong relationships with consumers. Thus, streamers can design more effective marketing strategies to encourage consumers to make repeat purchases and increase loyalty to the platform.